Research and Engineering Application of Key Waterproof Technology for Underground Stations with Assembled Superposed Structure - ZHU Jun; LIU Yi; PENG Yuyi; QIN Kai (Chengshi guidao jiaotong yanjiu)
［Objective］ Underground stations constructed in soil and rock layers are subject to long-term groundwater erosion and pressure infiltration. If waterproofing measures fail, water leakage issues may arise. Such leakage not only affects passenger experience and reduces operational service quality, but also poses risks to system equipment safety and shortens the service life of concrete structures. Therefore, it is essential to conduct in-depth research on key waterproofing technologies for underground stations with assembled superposed structure (abbreviated as AS station). ［Method］ Using the Nanmen Station of Wuxi-Jiangyin Intercity Rail Transit Project as a case study, an integrated ′three-in-one′ waterproofing system is proposed for AS stations. Experimental studies are conducted on two key technologies: the treatment of bonding surfaces between new and old concrete and the use of micro-expansion, low-shrinkage, crack-resistant concrete. ［Result & Conclusion］ Experimental results indicate that for bonding surfaces primarily under tensile forces, the water-washed aggregate exposure construction technique is more suitable, while for those under shear forces, the roughened surface construction technique is more appropriate. Additionally, concrete prepared with a combination of lightweight sand internal curing agents and expansive agents exhibits excellent low-shrinkage and crack-resistant performance.